HUBUNGAN ANTARA SELF-LOVE DENGAN KECERDASAN EMOSIONAL PADA REMAJA - Widowati, Kristina Widowati; Antonius Ian Bayu Setiawan (Jurnal Penelitian Ilmiah INTAJ, 2025)
The purpose of this study are, 1) to know how high the level of self-love in adolescents, 2) to know how high the level of emotional intelligence, 3) to analyse and know whether there is a relationship between self-love and emotional intelligence, 4) to know the items of self-love scale and emotional intelligence that are identified as low which can be proposed as a guidance topic. This research method is a quantitative correlation research, this research is aimed at adolescents in grade XI of Pangudi Luhur St Yusup High School Yogyakarta. Respondents in this study totalled 132 adolescents. The measuring instrument used is a survey as well as data collection instruments for two variables, namely self-love variables and emotional intelligence variables. Items were declared valid with the validity coefficient value, namely r ≥ 0.30 and p value < 0.05, and items were declared reliable when the reliability coefficient was greater than 0.70 (r1 > 0.70). The results of the study prove, 1) The level of self-love of adolescents in class XI of SMA Pangudi Luhur St. Yusup is high. It is shown from a total of 132 respondents 61 adolescents indicated a high level of self-love. 2) The level of emotional intelligence is indicated to be medium to high. It is shown that out of 132 respondents, 61 adolescents indicated moderate, 52 adolescents indicated a high level of emotional intelligence.3) There is a very strong and positive relationship with a high level of significance. Because the correlation value between the self-love variable and the emotional intelligence variable is 0.809 Furthermore, it is known that the significance value (Sig. 2-tailed) is 0.000. This confirms that the relationship is not coincidental, but has a strong and significant statistical basis. 4) It was found that the items of the self-love and emotional intelligence variables were indicated to be low, the self-love variable items proposed 3 guidance topic themes, and emotional intelligence proposed 3 guidance topics.